Gestión del conocimiento y su impacto en la ejecución del plan operativo anual en la dirección distrital 09d15 Empalme-Educación, año 2023-2024. - Moreira Segovia, Rosa Vanessa (2025)
This research explores how knowledge management influences the implementation of the Annual Operational Plan (POA) at the District Directorate of Education in Empalme 09D15 during the 2023–2024 period. The study focuses on three key aspects: the knowledge level of staff, organizational culture, and labor motivation strategies. The main objective is to assess the impact of knowledge management on POA execution, considering factors such as knowledge transfer, staff turnover, and institutional culture. A mixed-methods approach was adopted, combining qualitative and quantitative methodologies through inductive, deductive, and historical-logical methods. The study population consisted of 25 staff members, and data were collected through interviews, surveys, and direct observation. Findings reveal that only 30% of personnel are aware of the POA objectives, yet implementation reaches 100%, indicating a reliance on practical experience rather than formal knowledge. The absence of systematic mechanisms for knowledge documentation and transfer was identified, along with an organizational culture that limits collaboration and continuous learning. Additionally, a lack of incentives and recognition negatively affects employee motivation. The study recommends implementing continuous training programs, fostering an organizational culture supportive of knowledge sharing, and establishing motivation strategies, such as non-monetary recognition, to enhance performance. This research highlights the need to integrate knowledge management as a strategic tool to optimize POA implementation and ensure institutional sustainability.